Designing An Educatory Learning Model in The Islamic Boarding SchoolCommunity: Study of the Implementation of Islamic Education Values inEfforts to Handle Social Conflict - Ansori Ansori; Cahyaning Bhakti Utami; Achmad Abrari; Hosaini Hosaini; Lilik Puja Rahayu (Jurnal Medika: Medika, 2025)
This community service activity aims to foster harmony and strengthen friendship among the residents of Nogosari Village through religious activities. Based on observations and interviews with several local residents, the main issue identified is a lack of awareness about the importance of harmony, as well as the weakening of long-standing relationships due to various factors. To address this, the Participatory Action Research (PAR) model was applied, involving community members directly in identifying problems and implementing solutions. Through this approach, religious activities were organized as a medium to reconnect and unite the community. The results indicate a positive impact, as these religious gatherings have successfully encouraged interaction, mutual respect, and togetherness among residents. Furthermore, the effectiveness of these efforts is significantly enhanced when the activities are conducted regularly. By fostering spiritual and social bonds, religious events serve as a vital tool in restoring and maintaining harmony and friendship within the village, thus contributing to a more cohesive and peaceful community life in Nogosari.